Effects of Aspergillus oryzae α-amylase supplementation on rumen volatile fatty acid profile and relative abundance of mRNA associated with nutrient transporters in ruminal and duodenal tissue on beef steers - Gordon, Britney N., author; Engle, Terry E., advisor; Wagner, John J., advisor; Pritchett, James G., committee member (Colorado State University. Libraries, 2014)
The objective of this study was to investigate the impact of Aspergillus oryzae α-amylase (AAM) supplementation on rumen volatile fatty acid (VFA) profile and relative abundance of mRNA associated with nutrient absorption in ruminal and duodenal tissue from beef steers. Nine crossbred beef steers (BW 622 ± 50 kg), fitted with rumen and duodenal fistulas were used in this experiment. Steers were housed in individual stations and fed a high concentrate finishing diet (74.6% corn on a DM basis) twice daily for 8 d. Treatments included 1) CON (5 g corn meal; n=5) and 2) AAM (5g 750 fungal α-amylase units/g; n=4). Dietary treatment supplements were manufactured prior to each feeding by mixing 3 g of α-amylase or corn meal into 150 g of dried distiller's grains (DDG) for the AM feeding and 2 grams of α-amylase or corn meal into 100 g of DDG for the PM feeding. Supplements were applied as a top dress for every feeding and thoroughly mixed by hand. On d 5, rumen fluid samples were obtained every 4 h for 24 h and analyzed for VFA. On d 9, rumen papillae and duodenal mucosal tissue samples were collected. Total tissue RNA was extracted for real-time PCR analysis. Sodium/potassium ATPase pump α1, glucose transporter 2 and 5, putative anion transporter, isoform1, sodium/hydrogen antiporter isoforms1, 2 and 3, 3-hydroxy 3-methylglutaryl coenzyme A synthase isoform2, down regulated in adenoma, monocarboxylate co-transporter isoform1, and glyceraldehyde-3-phosphate dehydrogenase mRNA were tested. Relative expression (fold change) of mRNA in ruminal and duodenal tissues were analyzed using PROC GLM and VFA distribution was analyzed using PROC MIXED as a randomized block design with repeated measures. No treatment differences were detected for any of the genes analyzed in ruminal or duodenal tissue. Concentrations of VFA and the acetate to propionate ratio were similar across treatments. However, the acetate:propionate ratio and molar percentages of butyrate were numerically greater in AAM steers compared to controls. Under the conditions of this experiment, AAM supplementation had no impact on relative expression (fold change) of mRNA associated with nutrient absorption and minimal impacts on molar proportions of VFA.
Keywords: fungal Î±-amylase; duodenum; gene; rumen; steer; volatile fatty acids